Myocardiology in Africa - Kamunvi, F.; Ojiambo, H. P.; Bajusz, E. (East African Literature Bureau, 1974)
In 1971 the East African Medical Research Council, part of the East African Community Organization, sponsored an international symposium on preventive cardiology and cardiac metabolism. This conference was held in Nairobi, Kenya, and this volume is a record of the papers read there. It is intended to publish a further volume recording the participants' discussions.
Keywords: Cardiology and cardiac metabolism; Myocardiology